1995
DOI: 10.1117/12.210418
|View full text |Cite
|
Sign up to set email alerts
|

<title>Investigation into the origin of microbridging in chemically amplified negative-tone photoresists</title>

Abstract: Microbridge formation in a CAlViN photoresist we have developed is dependent on the ratio of dose to print ( DiP ) to dose to gel ( DTG ) as well as resist contrast. Photoresists formulated with poly(p-hydroxystyrene) (PHS) have a very high tendency to form microbridges when developed in 2.38 wt% TMAH due to high contrast and high a DTP/DTG ratio. When photoresists formulated from PHS were developed in 1 .2 wt% TMAH contrast and DTP/DTG ratio were reduced resulting in microbridging being nearly eliminated. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The low molecular weight fraction is assumed to inhibit the formation of insoluble resist segments. Linehan et al have reported that a diluted developer (1.2% TMAH) reduces microbridging [12]. We suppose the reason for their result is that the concentration of the developer is too low to isolate the resist segments, and the microbridges are not observed.…”
Section: Methodsmentioning
confidence: 89%
“…The low molecular weight fraction is assumed to inhibit the formation of insoluble resist segments. Linehan et al have reported that a diluted developer (1.2% TMAH) reduces microbridging [12]. We suppose the reason for their result is that the concentration of the developer is too low to isolate the resist segments, and the microbridges are not observed.…”
Section: Methodsmentioning
confidence: 89%
“…In our results, the onset of nano-edge roughness and microbridging occur at different polymer molecular weights suggesting that they are independent phenomena. Microbridging has been identified in similar negative-tone CA resist chemistries [19] [20] where its severity was shown to increase with higher polymer molecular weights and/or with stronger developer hydroxide concentration. We are unable to distinguish between these two possibilities with the CGR data now at hand.…”
Section: A Pairwise Comparison Of Selected Curves Inmentioning
confidence: 99%
“…Resolution of chemically amplified, negative-tone resists have been historically plagued by microbridging across narrow trenches. A study by Linehan et al suggests microbridging may be related to high resist contrast and a high ratio of dose-to-print to dose-to-gel 5 when the molecular weight was reduced 6 . Others have suggested that penetration of developer into the exposed, insoluble polymer matrix resulting in swelling may be to blame 7 .…”
Section: Introductionmentioning
confidence: 96%